POLA PENGGUNAAN SMARTPHONE REMAJA DESA GLAGAH, KECAMATAN TEMON, KABUPATEN KULON PROGO - Sudarman, Sudarman (Jurnal Ilmiah Multimedia dan Komunikasi, 2018)
This study aims to determine the Pattern of Youth Smartphone Use in Glagah Village, Temon District, Kulon Progo Regency. Smartphones are a very sophisticated development of communication technology in the current era of globalization, which gives users the flexibility to access information as well as communication to others, by providing very complex features. The ever-expanding smartphone technology is one of the technologies that can have a tremendous impact on the positive and negative sides. Because on the one hand it provides education to the public on the other hand destroying its user community. The research method used in this research is descriptive qualitative method by relying on logic and interpretive excavation. With the formulation of the problem What is the Pattern of the Use of Teenage Smartphones in Glagah Village, Temon District, Kulon Progo Regency. The result of the discussion, is that the pattern of the use of Teen Smartphone in Glagah village, Temon Subdistrict, Kulon Progo Regency is very alarming where the time pattern of smartphone use is very excessive, 4 hours and even some are infinite. education, entertainment, and 2 informants have said they saw negative sites. Most informants stated that they were used for excessive selfies. Parents ‘attitudes toward teenagers are often angry because they don’t always respond to orders from parents and even procrastinate from parents’ orders and don’t leave. Most of the achievements in using smartphones stated that the learning achievement had declined, only 1 informant stated that it had increased.